#Bopo: Enhancing body image through body positive social media- evidence to date and research directions. (June 2022) - Rodgers, Rachel F.; Wertheim, Eleanor H.; Paxton, Susan J.; Tylka, Tracy L.; Harriger, Jennifer A.
Abstract: Body positive content aims to disrupt the monopoly of idealized appearance-focused media and encourage individuals to adopt a positive stance towards their body by increasing diversity and inclusiveness and rejecting harmful appearance ideals. This paper provides an historical context for the body positivity movement, discusses the presence and characteristics of the online body positivity movement, presents evidence of its relationship to body image, and finally offers directions for future research. Findings provide initial support for the potential for body positive social media content to be beneficial for body image, and lower state appearance comparison has received support as a mechanism underpinning these effects. However, efforts to identify individual-level moderators have met with less success, and the research is somewhat confined to comparative effects with idealized social media content, and young women. Additional work to bridge the gaps in the extant data is needed. In particular, expanding the understanding of which types of body positive social media content can be most helpful to both prevent and decrease body image concerns and promote positive body image using a layered lens that considers the interactions of the individual, their context, and the type of body positive social media content will be most fruitful. Highlights: Body positive content aims to increase diversity and inclusiveness by rejecting harmful appearance ideals. Initial support for the potential for body positive social media content to be beneficial for body image exists. Lower state appearance comparison may underpin these effects. More work is needed to identify individual-level moderators.